Biochemical and Microbial Changes Associated with Fermentation of Setipinna phasa - Roy, Deepayan; Majumdar, Ranendra K; Maurya, Satyendra K; Tripathi, Hemant Hari (Fishery Technology, 2025)
Salt-free fermented Setipinna phasa, locally known as ‘phasa shidal’ is a traditional fish product of northeast India. This study was conducted to assess the biochemical and microbial changes during fermentation of S. Phasa. Moisture content, pH and crude protein of the fish product decreased, whereas, lipid and total titratable acidity increased during fermentation. There was no significant change in the total nitrogen content, however, protein nitrogen decreased significantly with the increase of non-protein nitrogen and alpha-amino nitrogen. The non-protein nitrogen to total nitrogen ratio also increased gradually from 16.62 to 37.96%. The lipid degradation products showed considerable increase during the fermentation process. The volatile nitrogenous bases showed a rapid increase in the beginning followed by a slow but gradual increase throughout the fermentation period and the value reached 231.94 mg of nitrogen 100 g-1 on 90th day. During the same period the microbial count increased rapidly in the beginning and reached 6.79 log cfu g-1 on 90th day. Staphylococcus spp. and Bacillus spp. were found to be the predominant groups of bacteria during fermentation. On 90th day, the product was moist with very soft surface and texture, moderate stickiness with strong characteristic smell of shidal.